Islamophobia and Acts of Extremism Against Muslim Minorities in Sri Lanka Before and During the Covid-19 Pandemic - Muhammad Saekul Mujahidin (IAIN Batusangkar, 2023)
Sri Lanka has witnessed many examples of anti-Muslim sentiment and violence since the end of the civil war, especially in 2014 when an ethnic outbreak affected large numbers of people. Sinhala monks and Buddhists appear to have played an important role in covering it. Long wars and ethnonationalist ideology have resulted in a politico-religious shift related to “Buddhist extremism”, which engages in embracing and attacking Muslims. This study uses the